Cerita Anak Bergambar untuk Mendukung Kegiatan Literasi yang Melibatkan Orang Tua Murid KB/TK Aisyiyah Bustanul Athfal 5 Malang - Febriyanti, Rike; Husna, Lailatul (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2023)
This study is to determine whether illustrated children's book can effectively address the issue of young learners' lack of interest in reading. Learning to read entails comprehending the written symbols that oral language sounds represent. Using a picture book is one of several ways that may be used to teach reading to young learners.  Three illustrated children's books influenced by Japanese culture are included in this periodical. The findings of this study demonstrate that, with the active assistance of their parents, picture books can enhance and encourage young learners to favor reading. Picture books teach kids to understand stories that require conversation and aid in their visualization of literacy.